IDENTIFIKASI D. MELANOGASTER PADA MEDIA BIAKAN ALAMI DARI PISANG SEPATU, BELIMBING DAN JAMBU BIJI - Rachmat Slamet Santoso (Universitas Tribhuwana Tunggadewi, 2011)
One cause damage to fruit on cultivated plants is the fruit fly, Drosophila sp. Losses caused by fruit fly Drosophila sp in Indonesia is still limited. But the FAO reports that in Japan has cost approximately 32 million U.S. dollars or IDR 250 trillion to control these fruit flies. Some researchers have obtained information about the food of predators (birds nest) as an insect the size below 5 mm. This research aims to identify and isolate D. melanogaster in a natural culture medium of shoes banana, star fruit and guava as well as knowing the number of population D. melanogaster as well as calorific value, proteins, fats, carbohydrates and minerals from the artificial media. The research was conducted in the Kamangta Village, Tombulu Minahasa District with a height of 500 m above the sea surface and air temperature ranges of 26- 30°C. The research lasted 18 months, starting from August 2008 until January 2010. The results of this research are: 1). showed that the natural medium of banana shoes to give more positive responses than the guava and star fruit and 2). larvae of the fly life cycle D. melanogaster from the egg into imago is 10 days old while the change from egg to imago vary depending on environmental conditions